The Effectiveness of MIKiR Approach in Mentoring Program For Lecturers during The Covid-19 Pandemic - Zulaikhah Zulaikhah; Ani Hidayati; Rosyidatul Fauziyah (FITK UIN Walisongo, 2022)
The study entitled the effectiveness of Mengalami-Interaksi-Komunikasi-Refleksi (MIKiR) approach on lecturers of the Tarbiyah and Teacher Training faculty (FITK) at the Walisongo State Islamic University, Semarang in the Covid-19 pandemic era and was aimed to examine the implementation of the method in a teaching mentoring program. The researchers employed a qualitative research method (field research) and collected primary data from interview data, observations, and documentation using Google Forms. The primary data collected include all documents related to the implementation and results of the mentoring program (RPS, lecture scenarios, LKM, lecture documents, etc). Secondary data consist of books and reference sources. The subjects of this study were FITK lecturers of the Walisongo State Islamic University, Semarang. Several stages of data processing were carried out: editing, classifying, verifying, analyzing, and concluding. The results showed that the mentoring program is relatively effective in helping the mentee lecturers in developing active learning using MIKiR approach.